Assertion-based analysis via slicing with ABETS* (system description). Issue 5 (14th October 2016) - ALPUENTE, M.; FRECHINA, F.; SAPIÑA, J.; BALLIS, D.
Abstract: We presentABETS, an assertion-based, dynamic analyzer that helps diagnose errors in Maude programs.ABETS uses slicing to automatically create reduced versions of both a run's execution trace and executed program, reduced versions in which any information that is not relevant to the bug currently being diagnosed is removed. In addition, ABETS employs runtime assertion checking to automate the identification of bugs so that whenever an assertion is violated, the system automatically infers accurate slicing criteria from the failure. We summarize the main services provided byABETS, which also include a novel assertion-based facility for program repair that generates suitable program fixes when a state invariant is violated. Finally, we provide an experimental evaluation that shows the performance and effectiveness of the system.